Women’s Language Features Used by The Female Main Character on It Ends with Us Novel - Arta, Putu Deta Yunia Hapsari; Matradewi, Ni Ketut Widhiarcani; Putra, I Komang Sumaryana (Apollo Project: Jurnal Ilmiah Program Studi Sastra Inggris, 2025)
This study entitled Women’s Language Feature Used by The Female Main Character on It Ends Us novel aims to explore the women’s language features and the function that was used by the female main character, Lily Bloom from Colleen Hoover’s Novel ‘It Ends with Us.’ A documentation method was applied as the method of collecting data, to analyze the data, a descriptive qualitative was applied, formal method used to present the analysis. The female lead character's conversation in the movie "It Ends with Us" was used as the source for the study's data. Additionally, the data were categorized and analyzed in accordance with various types of women's language as described in Lakoff's theory (1973). and the function of its feature was analyzed based on the theory of women’s language function by Pearson (1985) The findings of this study, from 10 language features, only 7 language features that used by the female main character, there are lexical hedge, tag question, empty adjectives, intensifiers, super polite forms, avoiding super strong swear words and empathic stress. In addition, there were four functions of women’s language found in this study such as to express uncertainty, to get response, to express a feeling and to soften an utterance. Keywords: Language Features, Main Character, Novel